Why is Tax Knowledge and Tax Understanding Important? - Susyanti, Jeni; Askandar, Noor Shodiq (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2019)
Micro, small, and medium (MSMEs) business play a crucial role in the economy of Indonesia. Unfortunately, there is low-income tax receipt from MSME sectors. This study examined the effect of taxation knowledge and understanding toward tax compliance among MSMEs owners, exclusively culinary business owners. The quantitative method was used in analyzing the data collected. The sample size for the research was 50, with all MSME owners responded through the questionnaire distributed. This study concluded that there is a positive effect between taxation knowledge and level of understanding toward tax compliance. It means that an increase in tax knowledge and tax understanding level can lead to an increase of tax compliance level. Although this study succeeded to prove the effect between variables, the results of secondary data indicate that many MSME owners are still confused in implementing tax regulations, PP-23/2018.Â